Farmer's lung in Northern Ireland. Issue 5 (May 1990) - Stanford, C F; Hall, G; Chivers, A; Martin, B; Nicholls, D P; Evans, J
Abstract : A total of 381 farmers in Northern Ireland were studied using a questionnaire, pulmonary function tests, and antibody levels to Micropolyspora faena to assess the incidence of farmer's lung. Twenty (4.9%) had a history of a previous diagnosis of farmer's lung by their doctor. Forty four (10.4%) had delayed onset symptoms compatible with farmer's lung, 32 (7.9%) had precipitant antibody, and 61 (15%) had raised antibody by the enzyme linked immunosorbent (ELISA) method. Restricted lungs were present physiologically in 40 (9.8%). A confirmation of delayed symptoms and precipitant antibody was present in seven (1.7%) whereas delayed symptoms and ELISA antibody was present in nine (2.2%). Using either antibody method only two (0.5%) had a combination of antibody to M faenae, delayed onset symptoms, and restricted pulmonary physiology.